The effect of sanitary restrictions on businesses in the city of Bejaia: Factorial analysis and logistic regression (ordered multinomial logit) - Zidat, Rafika; Amia, Nassira; Tighlit, Asma; Tighidet, Kenza (International journal of economic perspectives, 2024)
The objective of this research is to evaluate the commercial activity in the city of Bejaia before, during and after the lifting of the sanitary restrictions following the spread of COVID-19. First, the data for this study were collected through a field study that was conducted on the shops in the city of Bejaia, in order to identify the degree of impact of this pandemic on the region, and to collect all useful information that will serve as a solution to our problem. Then, we proceeded to analyse the collected data through a multiple correspondence factorial analysis, which allowed us to classify the companies as essential and non-essential. Finally, logistic modelling was used to discern the effect of health restrictions on businesses in the city. Non-essential businesses suffered significant losses in the different periods (during and after the restrictions were lifted).